PENINGKATAN KEMAMPUAN MEMBACA PETA DUNIA MENGGUNAKAN MEDIA PUZZLE BAGI SISWA KELAS VI SDN PEDALANGAN 02 KOTA SEMARANG TAHUN PELAJARAN 2014/2015 - Turasmi, Turasmi (Faculty of Social Science, Universitas Negeri Semarang, 2014)
Action researchinthe classroomVI SDN Pedalangan 02 Semarang year 2014/2015 by using the media puzzle aimed to improve students' ability to read the world map. The way the data was collected through Â observation, questionnaires, documentation of activities for students to learn and teachers through the use of game media, and students' work to determine student understanding through assessment/ evaluation. The results of prior research by the number of 38 students, who have reached the KKM (> 7) had 11 students (28.90%), while the remaining 27 (71.10%) students are not yet Media puzzles, learning base map complete. Student activity in learning is also very low, with only 12 students indicated that attention well, 4 active child asks, while the other passive. Seeing this fact then do the research and show improved results in reading maps world blind. Evidenced by tests in cycle 1, indicating as many as 22 students (57.90%) has reached mastery learning (> 7), while 16 students (42.10%) was not finished. Increased student activity shown by 31 (81.60%) students actively asked, 34 students are actively trying / learning media responds. With the results of tests on the first cycle has been no increase in yield, but not maximized. 2 Cycle to be done to improve the learning process in the first cycle and showed maximum improvement, from 38 students who have reached the KKM 35 students (92.1%), while the remaining try students (7.90%) was not finished. All students (100%) going to try to respond to the media or the media. Thus declared a class action meets the criteria expected in the second cycle. Suggested for educators in teaching and learning aids or media is very important, to planting concept on students. Media Puzzle is ideal to use in maps.